Introduction : The Volatility of Overseas Aid - Bulir, Ales; Gelb, Alan; Mosley, Paul (2012)
Evidence is mounting that the pattern of overseas aid through time, of which its volatility (or instability) is a key dimension, has an important influence on its effectiveness. The three papers in this special section examine the extent of this influence, and how it may be possible to control volatility in the interests of more effective aid.